2009
DOI: 10.1080/11038120802409762
|View full text |Cite
|
Sign up to set email alerts
|

Doing everyday life—experiences of the oldest old

Abstract: The purpose of this article is to explore how a group of elderly people, living and managing on their own, describe and experience their everyday doings. Interviews and observations were conducted with 18 community-living people aged 85 and above. The experiences of 'Doing everyday life' are described in five overarching themes: 'Experiencing being old', 'Doings in everyday life', 'Patterns of the day', 'Altered doings', and 'The importance of time'. What is done during an ordinary day does not differ much fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 27 publications
1
43
0
4
Order By: Relevance
“…Thus, temporal aspects are important factors for organizing patterns of occupations, integrating habits and routines into daily life (Larson & Zemke, 2003) and for experiencing health and well-being (Christiansen & Baum, 1997). Research has also shown the importance of daily routines for very old adults to experience health and well-being (Häggblom-Kronlö f et al, 2007;Larsson, Haglund, & Hagberg, 2009). …”
Section: Temporality For Health and Well-beingmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, temporal aspects are important factors for organizing patterns of occupations, integrating habits and routines into daily life (Larson & Zemke, 2003) and for experiencing health and well-being (Christiansen & Baum, 1997). Research has also shown the importance of daily routines for very old adults to experience health and well-being (Häggblom-Kronlö f et al, 2007;Larsson, Haglund, & Hagberg, 2009). …”
Section: Temporality For Health and Well-beingmentioning
confidence: 96%
“…Thus, there are reasons to believe that socio-temporal aspects have had substantial influences on the participants' temporal order of their PDO even after retirement. Qualitative studies have described how very old adults like to be in control and keep an organized daily routine (Larsson et al, 2009) and to follow perceived norms to keep healthy; for example, not giving in to fatigue or sleep during the day (Green, Sixsmith, DahlinIvanoff, & Sixsmith, 2005;Nilsson et al, 2012). Furthermore, interruption of daily routines can cause unpleasant experiences for very old adults (Häggblom-Kronlö f et al, 2007) and therefore it might be important to maintain and enable their established routines.…”
Section: Sequences Of Daily Occupation and Sleepmentioning
confidence: 99%
“…Changes occur, however, as part of the ageing process, both in relation to the variety, frequency and time spent on these activities (18). Even if older people's days usually consist of activities that always have been done, they also strive to perform these activities in a well-known way (19). For older men living alone it is important to have balance in everyday life and in social interaction with other men, but also to maintain a sense of purpose in life, for example, by helping other people or to perform different kinds of leisure activities (20 …”
Section: Introductionmentioning
confidence: 99%
“…These multiple cases were carried out in real life situations, i.e. activities in everyday life, which made it possible to understand the complexity of MDs use in different 19 social and physical contexts. The purpose of the narrative stories were to depict each participant and capture some of the changes over time in order to facilitate the understanding of each participant´s experiences of MDs use from the values and life he had lived.…”
mentioning
confidence: 99%
“…A positive life orientation is a decisive inner resource for the health and well-being of older people, including the ability to find meaning in life and look forward to and have plans for the future (Fagerström, 2010), even if older people have a tendency to appreciate small things in daily life (Andersson, Hallberg, & Edberg, 2008). In spite of age and decreasing health with reduced capacity and functional constraints, being occupied and staying healthy and of sound mind are considered important to manage most independently in the doings of everyday life as an oldest old person (Larsson, Haglund, & Hagberg, 2009). …”
Section: Discussionmentioning
confidence: 99%